Hubungan Keaktifan Berorganisasi dengan Manajemen Waktu dan Indeks Prestasi Kumulatif pada Mahasiswa Angkatan tahun 2013 di Fakultas Kedokteran Universitas Lampung - Rika Lisiswanti; Merry Indah Sari; Betta Kurniawan; Hendra Effendi (Medula, 2020)
Students have role as an agents of change by participating in organization without neglecting their academic achievement. Student’s academic achievement is measured by Grade Point Average (GPA). Students need a good skill to manage their time between academic activities, and organizational activities. We conduct research to determine the relationship of organizational participation with level of time management and GPA of students batch 2013 in Medical Faculy of Lampung University.This research method is a comparative and correlative analytic observational study with a cross-sectional approac. This research was conducted in June 2016 at the Faculty of Medicine, University of Lampung. The sample was selected by consecutive sampling and obtained 40 respondents for each student who was active and not active in organizing. The hypothesis test used was the Chi-square comparative test and the Gamma correlative test. The level of time management based on organizational participation showed no significant difference. There was a significant difference in the GPA based on the activeness of organizing with a better GPA on students who wereactive in organization. There was no relationship between the level of time management with the level of GPA.